Mitochondrial and metabolic remodelling in human skin fibroblasts in response to glucose availability. (7th March 2022) - Pinho, Sónia A.; Costa, Cláudio F.; Deus, Cláudia M.; Pinho, Sonia L. C.; Miranda‐Santos, Inês; Afonso, Gonçalo; Bagshaw, Olivia; Stuart, Jeffrey A.; Oliveira, Paulo J.; Cunha‐Oliveira, Teresa
Abstract : Cell culture conditions highly influence cell metabolism in vitro . This is relevant for preclinical assays, for which fibroblasts are an interesting cell model, with applications in regenerative medicine, diagnostics and therapeutic development for personalized medicine, and the validation of ingredients for cosmetics. Given these cells' short lifespan in culture, we aimed to identify the best cell culture conditions and promising markers to study mitochondrial health and stress in normal human dermal fibroblasts (NHDF). We tested the effect of reducing glucose concentration in the cell medium from high glucose (HGm) to a more physiological level [low glucose medium (LGm)], or its complete removal and replacement by galactose [medium that forces oxidative phosphorylation (OXPHOSm)], always in the presence of glutamine and pyruvate. We have demonstrated that only with OXPHOSm was it possible to observe the selective inhibition of mitochondrial adenosine triphosphate (ATP) production. This reliance on mitochondrial ATP was accompanied by changes in oxygen consumption rate and extracellular acidification rate, oxidation of citric acid cycle substrates, fatty acids, lactate, and other substrates, increased mitochondrial network extension and polarization, the increased protein content of voltage‐dependent anion channel (VDAC) and peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha and changes in several key transcripts related to energy metabolism. LGm did not promote significant metabolic changes in NHDF, although mitochondrial network extension and VDAC protein content were increased compared to HGm‐cultured cells. Our results indicate that short‐term adaptation to OXPHOSm is ideal for studying mitochondrial health and stress in NHDF. Abstract : Since cell culture conditions highly influence cell metabolism in vitro, we investigated the optimal conditions to assess mitochondrial function in human fibroblasts. Removal of glucose and replacement with galactose‐induced mitochondrial remodelling and cellular reliance on mitochondria for ATP production; reduction of glucose availability to physiological levels was adequate to promote mitochondrial network remodelling but not metabolic activity. Our results suggest that the removal and reduction of glucose have different effects.